The Psychometric Properties of the Norwegian version of Health of the Nation Outcome Scales for Children and Adolescents (HoNOSCA) - Richter, Jörg; Hanssen-Bauer, Ketil (PsykTestBarn, 2012)
Description: The Health of the Nation Outcome Scales for Children and Adolescents (HoNOSCA) is a mental health assessment tool developed to evaluate treatment in child and adolescent mental health services (CAMHS). The HoNOSCA is rated by clinicians, based on their evaluation of the child’s or adolescent’s (3 – 18 years old) mental health problems and symptoms. The original English version has been developed by Gowers, Harrington and Whitton, and was published in 1998. It was translated into Norwegian by Ketil Hanssen-Bauer, and independently back-translated by Torill Ueland. The Norwegian translation was approved by Simon Gowers (first author of the original version and leader of the HoNOSCA team at the University of Liverpool). The HoNOSCA was published under Crown Copyright in Great Britain. The Norwegian version is freely available via www.r-bup.no. The HoNOSCA consists of 15 scales each scored between 0 (no problem) and 4 (severe to very severe problem). Thirteen of the 15 scales are summed up to a total score indicating clinical severity. It takes less than 10 minutes to complete the HoNOSCA. It should be scored by persons with clinical competence in the field of child and adolescent mental health. A two-and-a-half-hour training is recommended. Literature search: Five publications of four Norwegian studies and one publication of a Danish study were included in this systematic review. The Norwegian publications reported the reliability based on 20 vignettes (169 scorers) and 30 patients (three scorers); the cross-national (Norway, Denmark, England, New Zealand, and Australia) reliability based on the same 20 vignettes (30 scorers); the validity by comparing responses to relevant questions from the ASEBA form for parents, teachers and adolescents (CBCL, TRF, and YSR) in 153 outpatients; and prospective data from 192 inpatients of acute adolescent psychiatric units. The Danish publication reported a prospective validation study comparing HoNOSCA data with data from the Global Assessment of Psychosocial Disability (GAPD) in 173 patients. Psychometrics: Inter-rater reliability varied considerably across the different scales, both for vignettes and patients. However, the reliability of the HoNOSCA total score was good for vignettes and acceptable for patients. Substantial group differences and substantial moderate correlation coefficients with corresponding scales of other standardized methods (ASEBA) indicate that the concurrent and criterion-related validity of the Norwegian version of HoNOSCA are good. Conclusion: The documentation of validity and reliability of the Norwegian version of HoNOSCA is good, but is based on studies by one research group only. More independent psychometric investigations are desirable. The findings show that the Norwegian version of HoNOSCA has good psychometric properties, in particular with respect to inter-rater reliability, sensitivity to change, and concurrent as well as criterion-related validity.